2014
DOI: 10.1158/1541-7786.mcr-13-0168
|View full text |Cite
|
Sign up to set email alerts
|

HSPC111 Governs Breast Cancer Growth by Regulating Ribosomal Biogenesis

Abstract: Activation of c-Myc plays a decisive role in the development of many human cancers. As a transcription factor, cMyc facilitates cell growth and proliferation by directly transcribing a multitude of targets, including rRNAs and ribosome proteins. However, how to elucidate the deregulation of rRNAs and ribosome proteins driven by c-Myc in cancer remains a significant challenge and thus warrants close investigation. In this report, a crucial role for the HSPC111 (NOP16) multiprotein complex in governing ribosomal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Somewhat unexpectedly we observed that NIC4 controls transcription of ribosomal pre-rRNA, implicating Notch4 in ribosome biogenesis, although the physiological consequences of this central cellular process, remains to be investigated. Together, these observations suggest an additional layer of regulation of Notch4 activity with implications for growth regulation in development and disease [40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat unexpectedly we observed that NIC4 controls transcription of ribosomal pre-rRNA, implicating Notch4 in ribosome biogenesis, although the physiological consequences of this central cellular process, remains to be investigated. Together, these observations suggest an additional layer of regulation of Notch4 activity with implications for growth regulation in development and disease [40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In metazoans such as rat, chicken, human and Caenorhabditis elegans, CK2 mRNA and protein expression and activity are particularly high in organs during the early stages of development, compared with their adult counterparts [35]. CK2 is also more active in tumor tissues that have rapid proliferation rates than in normal tissues [5,6]. Furthermore, proliferation demands an increment of protein synthesis, which correlates with an increase in ribosomal biogenesis [36] and requires extremely fine regulation of the synthesis of the required amounts of proteins and rRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of ribosomes within a cell depends upon the availability of their components; therefore, regulation of rRNA and ribosomal protein synthesis impact the status of ribosome biogenesis. Several factors can modulate rRNA synthesis through rDNA transcription, such as the cell growth rate, chromatin structure, rDNA copy number, nutritional status, growth factors and chemical stresses [1][2][3][4][5][6]. Studies in human cells have revealed that selectivity factor 1, which binds to the rDNA gene promoter and promotes recruitment of pol I [7], is regulated by casein kinase 2 (CK2), extracellular signal-regulated kinase and mTOR [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribozymes 11,12 and Mpn1 exonuclease 13 also form a cP-containing 3′-end in their cleaved RNA fragments. Such cP formations are not just the result of specific ribonuclease digestions, but cP formations themselves can have a functional significance: cP formations regulate RNA-protein interactions, RNA stability and turnover, and cell proliferation 7,1416 . In tRNA splicing, 3′-terminal cP of 5′-exons is an important intermediate which is processed by a cyclic phosphodiesterase for ligation with 3′-exons 17 .…”
Section: Introductionmentioning
confidence: 99%